PENGARUH TINGKAT KEPATUHAN SUMBER DAYA MANUSIA TERHADAP MUTU INTERNAL PELAYANAN LABORATORIUM DI PUSKESMAS KABUPATEN GARUT - Fitri Rahmi Fadhilah; Ni'matul Murtafia'ah (Jurnal Kesehatan Rajawali, 2021)
Compliance with human resources, in this case health workers, greatly affects the quality of health servicesin providing health services, therefore all health service processes are expected to refer to the establishedstandard operating procedures. Internal Quality Consolidation is a laboratory system to identify andminimize errors from Pre-Analytical, Analytical and Post-Analytical. This type of research aims todetermine the relationship between the level of compliance of human resources with the internal quality oflaboratory services at the Garut district health center. The method of this research is qualitative by usingthe analytical research method of rank sperman correlation with a total of 30 respondents conducted at thePuskesmas Laboratory in Garut district. The results of this study indicate that there is a relationship of 0.378between the level of compliance of human resources with the internal quality of laboratory services at theGarut district health center, with a level of closeness as evidenced by the coefficient of determination,namely 14.30%, the level of compliance of human resources with the internal quality of laboratory services.has a significant effect with p-value 0,040. The conclusion of this study is that there is a significant effectbetween the level of compliance of human resources to the internal quality of laboratory services at theGarut district health center.